Efektivitas Program Perlindungan Anak Perempuan dari Kekerasan Seksual: Studi Evaluatif pada Dinas PP dan PA Kota Medan - Yarli, Yosi; Suriadi , Agus (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Sexual violence against girls is a serious problem that needs to be addressed comprehensively. This study aims to evaluate the implementation of the program to protect girls from sexual violence carried out by the Medan City Office of Women's Empowerment, Child Protection, Community Empowerment and Population Control and Family Planning (DP3APMP2KB). This research uses a qualitative method with a descriptive approach. Data collection was conducted through in-depth interviews, observation, and documentation studies. The results showed that DP3APMP2KB of Medan City has implemented various programs such as socialization, victim assistance, and training for assistants. However, the implementation of the program still faces several obstacles, such as a lack of human resources, minimal budget, and low community participation. This study recommends the need for improvement in terms of resource allocation, especially in staff training and facility development, seeking additional funding sources to overcome budget limitations, improving inter-agency coordination by developing a more effective communication system and conducting programs aimed at eliminating social stigma against victims of sexual violence, as well as providing social support to victims of sexual violence.